SUSTAINABILITY THROUGH THE UTILIZATION OF WASTE: A STUDY OF PROCEDURES IMPLEMENTED IN A SUPERMARKET FOR MEDIUM SIZE - BRAGA JUNIOR, Sergio Silva; RIZZO, Marçal Rogério (Revista Brasileira de Engenharia de Biossistemas, 2010)
Improve the operation of the processes and income generating activities become relevant to support the company. Following this aspect supermarkets are expanding their responsibility to the consumer and looking to improve their processes. Aiming to analyze the processes that have been deployed for a supermarket in the state of Mato Grosso do Sul/Brazil and how they can be used to generate sustainability of the company, through a case study, the study demonstrated that environmental, social and economic gains generated by the implemented processes, can be exploited by other retail organizations who adopt this practice as an example.